Mortalidade por câncer de mama em mulheres no estado de Mato Grosso, 1996-2020 - Horn, Marcilei Juvenal da Conceição (2018)
Breast cancer is the malignant neoplasm with the highest incidence and mortality in the worldwide female population. Estimates indicate that breast cancer caused 522,000 deaths in 2012. In Brazil, breast cancer continues with the highest mortality rates due to neoplasia in women, reaching 16.30 / 100,000 in 2015. The objective of the present study was to analyze the evolution of mortality due to breast cancer in women in Mato Grosso State, from 1996 to 2020. This is a descriptive and ecological study of time series, with data from the Mortality Information System and population, obtained on the DATASUS website of the Brazilian Ministry of Health. The specific mortality rates were calculated and standardized by age for the state of Mato Grosso, capital and inner cities. The annual percentage change was estimated by the Prais-Winsten regression method and for the prevision was adopted the model ARIMA. There was an increasing tendency of mortality due to breast cancer in the whole Mato Grosso State with bigger annual percentage change in the inner cities. The same behavior was noticed in the mortality rates in women from 40 years old. The previsions indicated that rates will continue growing, showing the need to strengthen breast cancer control actions in Mato Grosso state.